Health Status and Life Satisfaction among Aging People in Kathmandu - Khanal, Kashi Nath (SMC Journal of Sociology, 2024)
Aging is a complex social process. It brings more complications and illnesses in human lives. Because of odds of getting ill rise in old age, chances of becoming disabled and of dying come close. However, healthy aging can also be enhanced via living an active life. Everyone desires for a happy and healthy life, and thus, there is reciprocal relationship in role, healthiness and happiness. Society also waits for healthy people, who can play active roles effectively in society. Performing social roles help people to remain healthy, and activeness help improve healthiness in their life. In this article, I discuss the situation of health and life-satisfaction among aging people in Kathmandu. This paper is prepared on fresh-handed data collected from 45 respondents by using random sampling method. It describes the interrelationship between people's role and their health. Peoples' health deteriorates once their age rise, but those people who had performed their assigned role were found to be happier and healthier than the idle people of the same age.